Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Asli Daerah Kabupaten Badung - Wijaya, Putu Adhi Guna; Yuliarmi, Ni Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 8, No. 2, Februari 2019, pp (239-485), 2019)
The tourism sector is one of the fastest growing sectors in the world. This study aims to analyze the influence of tourist visit, hotel room occupancy rate, and the number of residents simultaneously and partially to the original income of Badung regency. The data used in this study is secondary data, obtained from the Central Bureau of Statistics Badung. The analysis technique used in this research is multiple linear regression analysis. The simultaneous test results (F test) shows that tourist visits, hotel room occupancy rate, and the number of residents simultaneously have a positive and significant effect on the Badung District's Own Revenue. Partially (t test) indicates that tourist visit have positive and significant influence to Badung District Original Revenue. The occupancy rate of the hotel room has a positive and significant impact on the Badung District's Original Revenue. The number of residents has a positive and significant impact on the Badung District's Original Revenue. Referring to the results of research then the Local Government should increase revenue Original Regional revenue by exploring the potential of regional tourism and more firmly in the hotel restaurant tax collection.